ANALISIS RISIKO DAN PENGENDALIAN BAHAYA BENGKEL PEMESINAN DI SMKS PANCASILA SURAKARTA - Irvan Bayu Widyasmoro; Lutfi Ilunsa Zain; Joko Pamiyanto; Malikul Misbah; Muh fuad Adi Dwi cahyanto; Muhammad Agus Ma’ruf; Suwarta Suwarta; Danar Susilo Wijayanto; Valiant Lukad Perdana Sutrisno (Nozel : Jurnal Pendididikan Teknik Mesin, 2024)
This research aims to carry out an in-depth analysis regarding risks and work safety control efforts at the SMKS Pancasila Surakarta Machining Workshop, by applying the Job Safety Analysis (JSA) method. In the direct observation process, a number of potential risks have been identified, including aspects of lighting that are less than optimal, equipment storage management that is not yet fully efficient, conditions of supporting facilities that need to be improved, and a lack of awareness regarding Occupational Safety and Health (K3). This risk analysis then paves the way for the development of control measures that focus on improving lighting, better equipment storage arrangements, strategic placement of supporting facilities, installation of stabilizers on machines, and expanding K3 awareness through industrial work culture. It is hoped that these recommendations can make a significant contribution in creating a learning environment that is not only safe and comfortable, but also more productive for students and teaching staff in vocational school machining workshops. Thus, this research not only illustrates an in-depth understanding of risks in SMK machining workshops, but also offers concrete solutions to improve overall work safety conditions.